Evaluation of Sympathetic Skin Response and F Wave in Fibromyalgia Syndrome Patients - Tuncay ÇAKIR,; Deniz EVCİK,; Ümit DÜNDAR,; İlknur YİĞİT,; Vural KAVUNCU, (Archives of Rheumatology, 2011)
Objectives: This study was planned top erforman electroneuromyographic evaluation of the sympathetic skin response (SSR) and F wave in order to determine whether there is an autonomic dysfunction in fibromyalgia syndrome (FMS). Patients and methods: Thirty-eight patients (1 male, 37 females; mean age 40.6±9.6; range 22 to 60 years) who were admitted to our clinic between March 2005 and March 2006 and diagnosed with FMS and 30 healthy controls (1 male, 29 females; mean age 39.5±9.0 years; range 22 to 55 years) were enrolled in this study. After clinical examination, all patients were evaluated in the electroneuromyography (ENMG) laboratory with respect to SSR and F wave. The F wave was measured in both median and ulnar nerves. The SSR was evaluated in the median nerve. Patients were assessed with respect to the mean value of the F wave distal latency, the distal latency for SSR and the amplitude values. All patients were also evaluated for pain (Visual analogue scale, VAS), number of tender points (NTP), depression (Beck depression inventory, BDI) and functional capacity (fibromyalgia impact questionnaire, FIQ). Results: No statistically significant difference was found in the distal latency values of the F wave between the groups (p>0.05). Fibromyalgia syndrome patients were found to have significantly higher SSR amplitude values and lower latency values for both sides when compared with controls (p<0.05). No statistically significant correlation was found between the SSR (amplitude and latency), and F wave results and the VAS, BDI, FIQ and NTP scores in the patients with FMS (p>0.05). Conclusion: Our results support that, in the sympathetic nervous system of the patients with FMS, there is an alteration that shows the presence of autonomic dysfunction.